A Escuta de amor na escrita da dor: narrativa autobiográfica como processo catártico - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This work was carried out by means of a Bibliographic and Documentary Research, of exploratory nature, through a theoretical review, supported by a dialogue between the Systemic, Socio-Historical and Psychoanalytical approaches aiming at developing a reflection on the role of autobiographical narratives, as a process cathartic, for selfmutilating subjects. With the realization that there was a dialogue between students and teacher, carried out through self-narratives, produced by students and addressed to the Teacher, the research question arose: What is the role of autobiographical narratives as a cathartic process for the self-mutilating subject? After this stage, aiming to answer the question-problem, we tried to verify how the self-writing could act as a cathartic process, providing the re-elaboration of internalized pain and conflicts by self-mutilating subjects. For this, we proceed with the bibliographic review on self-mutilation and on how the subject appropriates written language, according to historical-cultural psychology, in order to identify the role of self-writing in the process of re-signifying the traumas suffered by the subject. Next, we record the close systemic relationship between microsystem, mesosystem and macrosystem and the adjusted social behavior of the person. We conducted a rigorous bibliographic survey aiming to build a dialogue between the authors who proposed to study the cathartic process through writing. We then elucidate the relationship established between the writing of the self as a projection of the self and the traumatic events, intimate life stories of this subject, insofar as we note the role of the autobiographical narrative as a cathartic process of the self-mutilating life stories. As a result, we could see how valuable the role of self-writing is, whether in verbal language or a variant of it, manifested through cuts in the body, as a way of expressing the feelings, pains and unconscious anxieties of self-mutilating subjects. Finally, we point to the aspect of the cathartic function of autobiography to externalize conflicts and re-elaborate them through writing.
Listening to love in writing of pain: autobiographical narrative as a cathartic process
Keywords: Narrativa Autobiográfica - Escuta de amor; Narrativa Autobiográfica - Catarse; Narrativa Autobiográfica - Escrita da dor; Autobiographical narrative - Listen to love; Autobiographical narrativ - Catharsis; Autobiographical narrative - Pain writing; LETRAS::TEORIA LITERARIA; LINGUISTICA::FISIOLOGIA DA LINGUAGEM